2016
DOI: 10.3390/antibiotics5040036
|View full text |Cite
|
Sign up to set email alerts
|

Pectocin M1 (PcaM1) Inhibits Escherichia coli Cell Growth and Peptidoglycan Biosynthesis through Periplasmic Expression

Abstract: Colicins are bacterial toxins produced by some Escherichia coli strains. They exhibit either enzymatic or pore-forming activity towards a very limited number of bacterial species, due to the high specificity of their reception and translocation systems. Yet, we succeeded in making the colicin M homologue from Pectobacterium carotovorum, pectocin M1 (PcaM1), capable of inhibiting E. coli cell growth by bypassing these reception and translocation steps. This goal was achieved through periplasmic expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…It should be pointed out that deviations from the prototypical catalytic ColM motif do not necessarily preclude bacteriocin functionality (30). In line with this, it was recently found that the pectobacterial ColM-type bacteriocin pectocin M1 and a mutant form with a modified catalytic motif both provoke cellular lysis when expressed in the periplasm of E. coli (48). By demonstrating that only the pectocin M1 wild type retains lipid II degradation activity, this study indicates that toxicity exerted by the ColM module may be more complex than merely enzymatic, as initially thought.…”
Section: Discussionmentioning
confidence: 78%
“…It should be pointed out that deviations from the prototypical catalytic ColM motif do not necessarily preclude bacteriocin functionality (30). In line with this, it was recently found that the pectobacterial ColM-type bacteriocin pectocin M1 and a mutant form with a modified catalytic motif both provoke cellular lysis when expressed in the periplasm of E. coli (48). By demonstrating that only the pectocin M1 wild type retains lipid II degradation activity, this study indicates that toxicity exerted by the ColM module may be more complex than merely enzymatic, as initially thought.…”
Section: Discussionmentioning
confidence: 78%
“…S1 ). In support of that, it was previously suggested that lytic activity of pectocin M1, when expressed in E. coli and secreted to the periplasm, does not require FkpA for killing ( 29 ). It cannot be excluded, however, that in some species another chaperone(s) provides assistance in activity-generating folding.…”
Section: Perspectivementioning
confidence: 70%
“…For this protein, phosphatase activity via a lipid II hydrolase assay remains to be assessed ( 20 ). Interestingly, even in a mutated pectocin M1 protein where lipid II degradation is abolished, the ColM module may still provoke cellular lysis when secreted to the periplasm, indicating that inhibition by ColM domains may not be based solely on the known catalytic activity ( 29 ). This is reminiscent of the collateral damage to membranes and membrane-bound complexes that can be caused by lipid II-binding antibiotics ( 16 ).…”
Section: Perspectivementioning
confidence: 99%
“…Colicin M and recently identified orthologs from Pseudomonas and Pectobacterium species form a unique family of bacteriocins interfering with the integrity of the cell wall by enzymatic degradation of peptidoglycan lipid intermediates (8,9,26). They exert their deleterious activity in the periplasm of the targeted cells, i.e., in the compartment where the peptidoglycan lipid II precursor is translocated and where it remains transiently accessible before being used for polymerization steps by the penicillin-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…tomato DC3000, and P. fluorescens Q8r1-96 strains, and the corresponding proteins, named PaeM, PsyM, and PflM, respectively, were purified and their lipid II-degrading activity was characterized (6). Two other members of the same family were also identified in Pectobacterium carotovorum (7,8). The homology between these different proteins was mainly observed in the second half of the protein sequence which corresponds to the enzymatic activity domain.…”
mentioning
confidence: 99%